The Impact of Low-Income Households, Domestic Debt and The Stock Market on the Economic Growth of South Africa - Matlala, Kamogelo Sello Saul; Ratombo, Ndivhuho Eunice (International Journal of Economics and Financial Issues, 2025)
This study investigates the impact of low-income households, domestic debt and the stock market on the economic growth of South Africa using annual time series data from 1999 to 2023. Formal unit root tests, such as the Augmented Dickey-Fuller test and the Phillips-Perron test, were used to determine whether a series is stationary or non-stationary. This study employed the autoregressive distributed lag (ARDL) technique to determine the long and short-run positive or negative relationship between the economic growth of South Africa and its low-income households, domestic debt, and the stock market. The results show a positive and statistically significant relationship between economic growth and low-income households in both periods. Furthermore, a positive and statistically insignificant relationship was detected between domestic debt and economic growth. The stock market reveals a negative and statistically insignificant influence on economic growth. The findings of this study provide original and important guidance that can be used to determine levels of subsidies for low-income households, healthy levels of domestic debt, and assist in aligning the required investment threshold in the stock market for the sake of South African economic growth. The findings provide an opportunity and direction for the necessary monetary and fiscal policies, which can boost economic growth using 99% which is the highest speed of adjustment. This study contributes to existing literature on economic growth and low-income households, domestic debt, and the stock market in South Africa, as a developing country.